HUBUNGAN MEKANISME KOPING DENGAN KEPATUHAN DIET PADA PENDERITA DIABETES MELLITUS (DM) - Baharuddin, Baharuddin; Bustami, Bustami; Anasril, Anasril (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The main treatment for patients with diabetes mellitus is diet therapy. Diet therapy is very important for people with diabetes mellitus, because by undergoing the right diet therapy, blood glucose levels and body weight can remain normal. Adaptive coping mechanisms can result in a better quality of life and positive actions. This study aims to determine the relationship between coping mechanisms and diet compliance in people with DM. The type of research used in this study is quantitative, with a cross-sectional study design. Data collection techniques used questionnaires. There were 78 respondents in this study. Data analysis used the Chi-Square test. The results showed that the majority of respondents had adaptive coping mechanisms, namely 64 people (82.1%), and most respondents adhered to the DM diet, namely 80.8%. The Chi-Square test results showed that there was a significant relationship between coping mechanisms and diet adherence with a p-value of 0.000 (p<0.05). It is recommended that the Trumon Community Health Center provide education on diet adherence and good coping mechanisms to DM patients